THE CONTRIBUTION OF COMPENSATION AND TRAINING AND EMPLOYEE DEVELOPMENT ON NET OPERATING INCOME AT PT ANGKASA PURA I (PERSERO) - PUTRI, AUDINA NUR AMALIA; ADI, PRAMONO HARI; AFIF, NUR CHOIRUL (INDONESIAN RESEARCH SOCIETY, 2018)
Human resource management becomes a important aspect for an organization's, because it is the human who built up and develop the organization, to achieve its objectives. Achieving a goals for the company depends not only on modern equipment, facilities and complete infrastructure, but depends on the people who carry out the work. The success of an organization is influenced by the performance of individual employees. Amongs the important functions of human resource management, one of the most important in achieving optimal performance in terms of operational revenue of an airport is the improvement of the quality of Human Resources. The improvement of human resources can be done with the provision of education and training. PT Angkasa Pura I (PERSERO) is a State Owned Enterprise (BUMN) that engaged an airports services that manage 13 airports in the Central Region to Eastern Indonesia. In a human resource management,compensation satisfaction also become an important aspect because satisfaction of compensation can influence employee's behavior to work more excited and high performance. This study is more focused on whether the cost that has been spent so far can really contributes to get a better in net operating income or in fact there is no significant linkage. The purpose of this research is to know and analyze the contribution of compensation and training and employee development on net operating income. The sample in this study are PT Angkasa Pura I annual report on the year 2017 with 13 branches airport. Data were analyzed using IBM SPSS software or PASW (Predictive Analytics SoftWare). The limitation in this study actually the data for training and employee development still minim. There is no detail about how much each training and development that company spend for that. so because of that we can really have a detail information about it.